Republic of Poland : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This report on Financial System Stability Assessment analyzes the financial sector issues, the regulatory and supervisory framework, macroeconomic risks, and the soundness of the financial system of Poland. This paper also describes the assessments of the banking, insurance, and securities regulations, and of the systemically important payment systems, as well as an assessment of the observance of the code of good practices on transparency of monetary and financial policies, and the great progress made in assimilating international best standards and practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet